3D geological characterization of the Hontomín CO2 storage site, Spain: Multidisciplinary approach from seismic, well-log and regional data - Alcalde, J.; Marzán, I.; Saura, E.; Martí, D.; Ayarza, P.; Juhlin, Christopher; Pérez-Estaún, A.; Carbonell, R. (Elsevier, 2014)
The first Spanish Technological Development plant for CO2 storage is currently under development in Hontomín (Spain), in a fractured carbonate reservoir. The subsurface 3D geological structures of the Hontomín site were interpreted using well-log and 3D seismic reflection data. A shallow low velocity zone affects the wave propagation and decreases the coherency of the underlying seismic reflections, deteriorating the quality of the seismic data, and thus preventing a straightforward seismic interpretation. In order to provide a fully constrained model, a geologically supervised interpretation was carried out. In particular, a conceptual geological model was derived from an exhaustive well-logging analysis. This conceptual model was then improved throughout a detailed seismic facies analysis on selected seismic sections crossing the seismic wells and in consistency with the regional geology, leading to the interpretation of the entire 3D seismic volume. This procedure allowed characterizing nine main geological levels and four main fault sets. Thus, the stratigraphic sequence of the area and the geometries of the subsurface structures were defined. The resulting depth-converted 3D geological model allowed us to estimate a maximum CO2 storage capacity of 5.85 Mt. This work provides a 3D geological model of the Hontomín subsurface, which is a challenging case study of CO2 storage in a complex fractured carbonate reservoir.